Amazon green recovery and labor market in Brazil: Can green spending reduce gender and race inequalities? - Pedro Romero Marques; Luiza Nassif Pires; Tainari Taioka; José Bergamin; Gilberto Tadeu Lima (Levy Economics Institute of Bard College, 2024)
Announced in June 2021, the never-implemented Green Recovery Plan for the Brazilian Legal Amazon Region (GRP) would be a green transition initiative to be carried out by the state governments of the region. The GRP represented the first large-scale proposal aiming at the transition to a low-carbon economy in Brazil and offered a preliminary framework to evaluate the opportunities and limitations of green development in Global South economies. The GRP's initial phase would provide an investment of 1.5 billion reais (around 315 million in September 2023) in four areas: control of illegal deforestation, sustainable development, green technology, and green infrastructure. This article presents a counterfactual analysis by assessing the impacts of green spending in Amazon on the labor market, quantitatively-in terms of the number of jobs created-and qualitatively-exploring the distribution of those jobs by region and according to gender and race categories. We build synthetic sectors representing each area of investment in a two-region input-output matrix ("Brazilian Amazon" and "Rest of Brazil"). Using employment multipliers, we simulate a demand shock on the Amazonian economy and its impact on job creation in the two regions. Results suggest that green spending in the Amazon offers good perspectives (but also highlights limitations) for a just transition to a low-carbon economy in Brazil: the effects on employment favored the female workforce (both black and white) relative to the male and black workforce in the Amazon, leading to inequality-reducing composition changes in the Brazilian workforce as whole.
Keywords: J15; Q57; Q58; R11; R53; R58; 330; Green and just transition; Brazilian Amazon; employment multipliers; green spending